The evolution and expression of panarthropod frizzled genes - Janssen, Ralf; Schönauer, Anna; Weber, Melanie; Turetzek, Natascha; Hogvall, Matthias; Goss, Georgina E.; Patel, Neel H.; McGregor, Alistair P.; Hilbrant, Maarten (Frontiers in Ecology and Evolution, 2015)
Wnt signaling regulates many important processes during metazoan development. It has been shown that Wnt ligands represent an ancient and diverse family of proteins that likely function in complex signaling landscapes to induce target cells via receptors including those of the Frizzled (Fz) family. The four subfamilies of Fz receptors also evolved early in metazoan evolution. To date, Fz receptors have been characterised mainly in mammals, the nematode Caenorhabditis elegans and insects such as Drosophila melanogaster. To compare these findings with other metazoans, we explored the repertoire of fz genes in three panarthropod species: Parasteatoda tepidariorum, Glomeris marginata and Euperipatoides kanangrensis, representing the Chelicerata, Myriapoda and Onychophora respectively. We found that these three diverse panarthropods each have four fz genes, with representatives of all four metazoan fz subfamilies found in Glomeris and Euperipatoides, while Parasteatoda does not have a fz3 gene, but has two fz4 paralogues. Furthermore we characterized the expression patterns of all the fz genes among these animals. Our results exemplify the evolutionary diversity of Fz receptors and reveals conserved and divergent aspects of their protein sequences and expression patterns among panarthropods; thus providing new insights into the evolution of Wnt signaling more generally.